Sustainable development – the goal or source of global progress - Ristanović, Vladimir; Tošović-Stevanović, Aleksandra (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional Development, 2021)
One of the most important concepts of the development of the modern world is the successful conception of development policy and the identification of the impulse of sustainable development. Previous growth and development theories, based on quantitative theories and only economic growth determinants, are outdated from today's perspective and less in use. Contemporary world implies a holistic approach to development, according to which the priority is the formation of a coherent national development policy in line with the UN Agenda 2030. The focus of the analysis of the paper is on sustainable development indicators. The aim is to consider the effects of certain sustainable development indicators, to analyse the indicators at the EU level and confirm the importance of introducing the indicators into the national development strategy. The results of the analysis have proved that more flexible economic systems displayed a higher level of efficiency and reached a high level of the value of the set sustainable development indicators. The introduction of new sustainable development indicators at the national level can become imperative for future researches.